Study of the Resource Integration and Performance Improvement Strategies of Vocational Colleges in the Background of the Double High Plan in Xuzhou - Zhongxu Li; Jacky Mong Kwan Watt (International Journal of Economics and Management Sciences, 2025)
Under the Double High Plan, the management of vocational colleges in Xuzhou should focus on a few essential strategies to improve performance and use resources effectively. First, college leaders need to align their programs with local industry needs. By partnering with businesses and industry groups, colleges can adjust their curricula to keep them relevant, helping students find jobs and be satisfied with their education. Next, effective resource use is crucial. Managers should wisely allocate financial, human, and technological resources to create better learning environments. This may include training teachers to use new technologies and teaching methods, which can improve teaching quality and lead to better student outcomes. In addition, colleges should consistently apply strategies to improve performance. This includes ongoing professional development for teachers to help them deliver engaging and practical instruction. School managers should also regularly review and adapt these strategies based on student feedback and performance data to ensure they are effective. In summary, vocational colleges under the Double High Plan must use resources effectively and apply performance improvement strategies based on the research results of 375 Xuzhou vocational school employees. By being proactive and flexible, college managers can enhance educational quality and support student success in Xuzhou